Network analysis for food safety: Quantitative and structural study of data gathered through the RASFF system in the European Union. (March 2023) - Nogales, Alberto; Mora-Cantallops, Marçal; Díaz Morón, Rodrigo; García-Tejedor, Álvaro J.
Abstract: This paper reports a quantitative and structural analysis of data gathered on the food issues reported by the European Union members over the last forty years. The study applies statistical measures and network analysis techniques. For this purpose, a graph was constructed of how different contaminated products have been distributed through countries. The work aims to leverage insights into the structure formed by the involvement of European countries in the exchange of goods that can cause problems for populations. The results obtained show the roles of different countries in the detection of sensitive routes. In particular, the analysis identifies problematic origin countries, such as China or Turkey, whereas European countries, in general, do have good border control policies for the import/export of food. Highlights: A statistical and structural analysis of historical data on European food issues. Study of most sensitive countries and hazards, diameter, density, and type of network. Graph is weakly connected, connected components, and average clustering coefficient. In-degree and out-degree explain the role of countries in the trade chain.